Language Effects in Trilinguals: An ERP Study - Aparicio, Xavier; Midgley, Katherine; Holcomb, Phillip J.; Pu, He; Lavaur, Jean-Marc; Grainger, Jonathan (Frontiers in Psychology, 2012)
Event-related potentials were recorded during the visual presentation of words in the three languages of French-English-Spanish trilinguals. Participants monitored a mixed list of unrelated non-cognate words in the three languages while performing a semantic categorization task. Words in L1 generated earlier N400 peak amplitudes than both L2 and L3 words, which peaked together. On the other hand, L2 and L3 words did differ significantly in terms of N400 amplitude, with L3 words generating greater mean amplitudes compared with L2 words. We interpret the effects of peak N400 latency as reflecting the special status of the L1 relative to later acquired languages, rather than proficiency in that language per se. On the other hand, the mean amplitude difference between L2 and L3 is thought to reflect different levels of fluency in these two languages.